2020
DOI: 10.1051/0004-6361/201936634
|View full text |Cite
|
Sign up to set email alerts
|

The ALMA view of the high-redshift relation between supermassive black holes and their host galaxies

Abstract: Context. The existence of tight correlations between supermassive black holes (BHs) and their host galaxies properties in the local Universe suggests a closely linked evolution. Investigating these relations up to the high redshifts (z 6) is crucial to understand the interplay between star-formation and BH growth across the cosmic time and to set constraints on galaxy formation and evolution models. In this work we focus on the relation between BH mass (M BH ) and the dynamical mass (M dyn ) of the host galaxy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 144 publications
(304 reference statements)
12
66
1
Order By: Relevance
“…A vast sample of rotating galaxies has been well studied at < 4 (e.g., Epinat et al 2008;Förster Schreiber et al 2009;Gnerucci et al 2011), revealing dynamical masses and empirical scaling relations. While a number of clumpy or merging galaxies have been detected at > 4 (e.g., Carniani et al 2018;Pavesi et al 2018;Díaz-Santos et al 2018), and a handful of rotating starburst or quasar host galaxies at ∼ 4 − 6 have been well-modelled (e.g., Jones et al 2017;Pensabene et al 2020;Tadaki et al 2020;Fraternali et al 2021;Lelli et al 2021), only two unlensed rotating main sequence galaxies have been observed at ∼ 4 − 6: HZ9 (Capak et al 2015) and J0817 (Neeleman et al 2017(Neeleman et al , 2020 5 . In this section, we add six new ∼ 4 − 6 rotators from the ALPINE sample to this class: CG32, DC396844, DC494057, DC552206, DC881725, and VC.7875.…”
Section: Main Sequence Rotators At Z>4mentioning
confidence: 99%
“…A vast sample of rotating galaxies has been well studied at < 4 (e.g., Epinat et al 2008;Förster Schreiber et al 2009;Gnerucci et al 2011), revealing dynamical masses and empirical scaling relations. While a number of clumpy or merging galaxies have been detected at > 4 (e.g., Carniani et al 2018;Pavesi et al 2018;Díaz-Santos et al 2018), and a handful of rotating starburst or quasar host galaxies at ∼ 4 − 6 have been well-modelled (e.g., Jones et al 2017;Pensabene et al 2020;Tadaki et al 2020;Fraternali et al 2021;Lelli et al 2021), only two unlensed rotating main sequence galaxies have been observed at ∼ 4 − 6: HZ9 (Capak et al 2015) and J0817 (Neeleman et al 2017(Neeleman et al , 2020 5 . In this section, we add six new ∼ 4 − 6 rotators from the ALPINE sample to this class: CG32, DC396844, DC494057, DC552206, DC881725, and VC.7875.…”
Section: Main Sequence Rotators At Z>4mentioning
confidence: 99%
“…While the MS is not well constrained at z  5, we compare the SFR of J1243+0100 and other HSC quasars (Izumi et al 2018(Izumi et al , 2019 and optically luminous quasars at z  6 (Decarli et al 2018) with the MS at z ∼ 6 (Salmon et al 2015). Here we assume M dyn = M å , as is frequently done in z > 6 quasar studies (e.g., Wang et al 2013;Willott et al 2015;Venemans et al 2016;Pensabene et al 2020). The dynamical masses of course have large uncertainties and represent an upper limit to the stellar mass.…”
Section: Comparison Of the Star-forming Naturementioning
confidence: 99%
“…High-resolution interferometric observations predominantly performed by the Atacama Large Millimeter/submillimeter Array (ALMA) have allowed studies of cold gas dynamics in quasar host galaxies (Wang et al 2013;Venemans et al 2016;Decarli et al 2018;Pensabene et al 2020). These studies revealed that z  6 optically luminous (M 1450  −26 mag) quasars have, on average, ∼10× more massive SMBHs than the local coevolution relations for a given velocity dispersion and/or dynamical mass of the host, suggesting that SMBHs were formed significantly earlier than their host galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…The 158-mm emission line of singly ionized carbon, [C II], is a major coolant of the interstellar medium of galaxies and traces a combination of atomic and molecular hydrogen phases. The [C II] line has been observed up to z ≃ 7:5 (5), and several rotating disks have been identified at z > 3 (6)(7)(8). Most existing observations only marginally resolve the [C II] distribution and kinematics, and thus cannot distinguish between rotating disks, galaxy mergers, or gas inflows and outflows.…”
mentioning
confidence: 99%
“…The two additional components (bulge and DM halo) are modeled with analytic functions (9). The bulge component implicitly includes the contribution of the central supermassive black hole, which contributes <10% of the central mass in high-z galaxies (8).…”
mentioning
confidence: 99%